2006
DOI: 10.1007/s10661-006-9385-4
|View full text |Cite
|
Sign up to set email alerts
|

Metals Associated with Suspended Sediments in Lakes Erie and Ontario, 2000–2002

Abstract: Sediment traps were deployed in the three major basins of Lake Erie, and the central (Mississauga) basin of Lake Ontario, and refurbished seasonally over the period 2000-2002. In Lake Ontario, sediment down-flux rates and corresponding contaminant down-flux rates were highest in winter during periods of unstratified thermal conditions, and generally increased with depth due to the influence of resuspended bottom sediments during all sampling periods. Lake Ontario suspended sediments exhibited the highest conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…The influence of atmospheric contamination, as gauged from the percentage of masked pixels in the SeaWiFS dataset, does not vary substantially among the three basins, suggesting that, while some of the residual scatter observed with the regional algorithms may be due to unresolved atmospheric effects, it is likely that most of the residual scatter in the central and western basins is due to other factors. The western basin is known to have high loads of suspended sediment (Kemp et al, 1977;Marvin et al, 2007), and to have relatively high concentrations of algae with multiple accessory pigments (Ghadouani and Smith, 2005). These can confound the satellite signal, making it difficult to separate chlorophyll a from other CPAs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The influence of atmospheric contamination, as gauged from the percentage of masked pixels in the SeaWiFS dataset, does not vary substantially among the three basins, suggesting that, while some of the residual scatter observed with the regional algorithms may be due to unresolved atmospheric effects, it is likely that most of the residual scatter in the central and western basins is due to other factors. The western basin is known to have high loads of suspended sediment (Kemp et al, 1977;Marvin et al, 2007), and to have relatively high concentrations of algae with multiple accessory pigments (Ghadouani and Smith, 2005). These can confound the satellite signal, making it difficult to separate chlorophyll a from other CPAs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these variations in biological properties, most of the major rivers draining into Lake Erie empty into the western basin, where they deposit much of their accumulated sediment load (Kemp et al, 1977). This flux, and the resuspension of bottom sediments (Dusini et al, 2009;Marvin et al, 2007), contribute to the higher levels of turbidity observed in the shallow western basin as compared with other basins of the lake (Markarewiczl et al, 1999). Suspended sediments are a particular concern as they can be carriers of chemical contaminants (Marvin et al, 2002(Marvin et al, , 2004(Marvin et al, , 2007Painter et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Ankley et al (1996) showed bioturbation can cause oxidation of acid volatile sulfide, thereby altering the partitioning of sediment-associated metals like Cd and enhancing their bioavailability. In addition, Marvin et al (2007) noted that suspended sediments in the western Lake Erie basin were largely resuspended bottom sediments; hence, through bioturbation, mayfly nymphs may increase resuspended toxic contaminants (Bartsch et al, 1999;Bachteram et al, 2005), which increases Cd exposure for other aquatic organisms in the water column, including fish that may then take in Cd even without direct ingestion of mayflies. Based on the high Cd levels found in sediments in this study, the effect of mayflies on bioturbation is also of concern.…”
Section: Hexageniamentioning
confidence: 99%
“…These contaminants also have the potential for resuspension into the water column. Marvin et al (2007) found that contaminated suspended sediments from the western basin of Lake Erie are heavily influenced by resuspended bottom sediments. Correspondingly, mayfly nymphs have the potential for facilitating resuspension of sediment-bound contaminants through bioturbation (Bartsch et al, 1999;Bachteram et al, 2005), particularly in spring during their emergence.…”
Section: Introductionmentioning
confidence: 99%